2012
DOI: 10.1080/09205063.2012.714726
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of PLA/CDHA composite coating via electrospraying

Abstract: Composite coatings composed of carbonated calcium deficient hydroxyapatite (CDHA) and polylactic acid (PLA) were deposited on a PLA substrate surface via electrospraying. The operation parameters, structural properties, bioactivity, cell adhesion, and growth capability of as-fabricated PLA/CDHA coatings were investigated. The composite coating showed good biocompatibility and bioactivity. The deposited coating was also applied as a carrier to assist alendronate sodium (AS) local release. AS, an approved bispho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…During electrospinning, the organic solvent, which could be toxic to cells, will be completely evaporated due to its high volatility [22]. Electrospraying has similar preparation process to electrospinning but is usually used with higher voltage and lower polymer density, which makes the polymer solution more easily broken up into droplets [23, 24]. The concept of electrospraying process was used to increase layer-to-layer adhesion, which could avoid drug-storing layer cracking and separating from backing layer during the stent expending.…”
Section: Resultsmentioning
confidence: 99%
“…During electrospinning, the organic solvent, which could be toxic to cells, will be completely evaporated due to its high volatility [22]. Electrospraying has similar preparation process to electrospinning but is usually used with higher voltage and lower polymer density, which makes the polymer solution more easily broken up into droplets [23, 24]. The concept of electrospraying process was used to increase layer-to-layer adhesion, which could avoid drug-storing layer cracking and separating from backing layer during the stent expending.…”
Section: Resultsmentioning
confidence: 99%
“…Using the surface modification of physical deposition technique and wet chemical deposition technique to form the calcium phosphate (CaP) or HA coatings is a very attractive approach because BPs have a marked affinity to the substances [ 91 ]. Alternatively, the polymer coatings, including layer-by-layer (LBL), polymer brushes, dip coating, Langmuir–Blodgett, spin, and plasma-based coating methods, are also capable of loading BPs [ 92 , 93 ]. In this section, we focus on the mechanism of fabricating BP-coated implants ( Table 1 ) .…”
Section: Methods Of Fabricating Bp-coated Implantsmentioning
confidence: 99%
“…After 24 h, samples without PCL coating released >75% of ALN, and those with the PCL coating released approximately 50%. Moreover, composite coatings composed of CDHA, polylactic acid (PLA), and ALN were deposited on implants via electrospraying, which can control the slow release of ALN and promote osteogenesis [ 93 ]. Due to the prevention of the initial burst release of the PCL coating, the TCP-ALN-PCL composite coating scaffolds inhibited OC activity and promoted higher bone formation [ 228 ].…”
Section: Role Of Bps As Coatings To Promote Osseointegrationmentioning
confidence: 99%
“…It is reported that ZnO particles deposited 'on' PLA fibers surface are more efficient against microbiological tests than that of type 'in' mats which were mainly seen in the fibers bulk. Zhou et al [201] found that PLA/CDHA coatings performed by electrospraying are PLA/CDHA coatings are favored by osteoblast cells and promoted bone formation while delivering the drugs locally. With PLA/HA as electrospun nanocomposites, Prabhakaran et al [170] have studied and demonstrated that ECM production, mineralization and subsequent tissue regeneration properties have improved to a larger extent.…”
Section: Electrospun Polymeric and Nanocomposite Particles For Ammentioning
confidence: 99%